Influence of Microorganisms on the Healing of Skin Grafts from Chronic Venous Leg Wounds - Wolff, Tine Yding; Bjarnsholt, Thomas; Kirketerp-Møller, Klaus; Thomsen, Trine Rolighed (IntechOpen, 2011)
None